PEMANFAATAN TIKTOK LIVE SEBAGAI MEDIA KOMUNIKASI PEMASARAN DIGITAL DALAM MENINGKATKAN PENJUALAN BAJU BEKAS(THRIFTING) DITINJAU DARI PERSPEKTIF MANAJEMEN PEMASARAN SYARIAH - Muhammad Fasichul Lisan; Darul Islam; Achmad Fahim (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2025)
The development of digital technology has transformed marketing strategies, including the use of TikTok Live as an interactive communication medium between businesses and consumers. This study aims to analyze the utilization of TikTok Live in increasing secondhand clothing (thrifting) sales by the ft.Second store, as well as to evaluate its alignment with the principles of Islamic marketing management. A qualitative descriptive method was employed, with data collected through observation, in-depth interviews, and documentation. The findings show that TikTok Live effectively enhances consumer engagement and trust, contributing to a significant increase in sales. Moreover, ft.Second applies Islamic values such as shiddiq (truthfulness), amanah (trustworthiness), tabligh (transparency), and fathanah (wisdom) in its marketing activities. In conclusion, TikTok Live serves as a digital marketing strategy that is not only effective but also in line with ethical principles in Islamic marketing management.